Avaliação do efeito carcinogênico de edulcorantes por meio do teste para detecção de clones de tumores epiteliais (warts) em Drosophila melanogaster - Vasconcelos, Mirley Alves (2016)
The sweeteners may be nutritious and non-nutritious, natural or synthetic, the latter being sweeter compared to table sugar. These natural compounds have increased use to be safer, although this security can not be considered complete. The most consumed sweeteners are noncaloric, including aspartame, sucralose, sodium saccharin and steviol glycoside. Such substances have always been the target of studies related to genotoxicity, but getting inconclusive results encourage new tests that address the principles of genetic toxicology. This study was conducted in order to evaluate the carcinogenic potential of sweeteners by testing for the detection of epithelial tumor clones (warts) in Drosophila melanogaster. descendants larvae were used crossing virgin females wts / TM3 with male mwh / mwh, that have been chronically treated with a negative control (reverse osmosis water), one positive control doxorubicin (DXR) at 0.4 mM and five different concentrations of aspartame (0.85; 1.7; 3.4; 6.8 and 13.6 mM), sucralose (0,5; 1,25; 2,5; 5,0 and 10 mM), sodium saccharin (25, 50; 100; 200 and 400mM) and steviol glycoside (2.5, 5.0, 10, 20 and 40mM) separately. The results showed no statistically significant difference (p> 0.05) in the frequency of tumors observed in subjects treated with aspartame, sucralose, saccharin and steviol glycoside when compared to the negative control. It follows therefore that in these experimental conditions and the model organism Drosophila melanogaster, the sweeteners four tested did not induce tumor formation.